Constructing Co@TiO2 Nanoarray Heterostructure with Schottky Contact for Selective Electrocatalytic Nitrate Reduction to Ammonia. Issue 17 (30th January 2023) - Fan, Xiaoya; Zhao, Donglin; Deng, Zhiqin; Zhang, Longcheng; Li, Jun; Li, Zerong; Sun, Shengjun; Luo, Yongsong; Zheng, Dongdong; Wang, Yan; Ying, Binwu; Zhang, Jing; et al.
Abstract: Electrochemical nitrate (NO3 − ) reduction reaction (NO3 − RR) is a potential sustainable route for large‐scale ambient ammonia (NH3 ) synthesis and regulating the nitrogen cycle. However, as this reaction involves multi‐electron transfer steps, it urgently needs efficient electrocatalysts on promoting NH3  selectivity. Herein, a rational design of Co nanoparticles anchored on TiO2  nanobelt array on titanium plate (Co@TiO2 /TP) is presented as a high‐efficiency electrocatalyst for NO3 − RR. Density theory calculations demonstrate that the constructed Schottky heterostructures coupling metallic Co with semiconductor TiO2  develop a built‐in electric field, which can accelerate the rate determining step and facilitate NO3 − adsorption, ensuring the selective conversion to NH3 . Expectantly, the Co@TiO2 /TP electrocatalyst attains an excellent Faradaic efficiency of 96.7% and a high NH3  yield of 800.0 µmol h −1  cm −2  under neutral solution. More importantly, Co@TiO2 /TP heterostructure catalyst also presents a remarkable stability in 50‐h electrolysis test. Abstract : The Co@TiO2 /TP acts as a highly selective and durable electrocatalyst toward converting NO3 ‐ to NH3  in neutral media, achieving a high Faradaic efficiency of 96.7% and a large NH3  yield of up to 800.0 µmol h −1  cm −2 .